(untitled) (Research, Society and Development, 2021)
Training is one of the tools for improving the skills and competences of professionals who work in different organizations; thus the company has better technical conditions to develop its activities producing positive results. The general objective of this research was to identify the need for training employees of the company Micrológica, in Formosa-Go. The methodology used was the application of a questionnaire offered to employees of that company during a period of 10 days, where everyone had access to the research instrument; and given the data obtained, it was possible to identify the variables that affect the entire production process, in addition to offering conditions for them to improve their activities.